30 Years of International Higher Education, a Field of Study and a Publication - de Wit, Hans; Altbach, Phil (International Higher Education, 2025)
<h3 id="over-the-past-30-years-and-123-issues-of-international-higher-education-both-the-world-and-higher-education-have-changed-enormously-the-publication-has-both-followed-these-changes-and-made-adaptations-to-them-but-in-essence-its-guiding-principles-as-well-as-its-unique-position-have-remained-the-same" data-pm-slice="1 1 []">Over the past 30 years and 123 issues of International Higher Education, both the world and higher education have changed enormously. The publication has both followed these changes and made adaptations to them, but, in essence, its guiding principles, as well as its unique position, have remained the same.